ANALISIS PENGARUH INOVASI, PENGAMBILAN RESIKO, OTONOMI, DAN REAKSI PROAKTIF TERHADAP KAPABILITAS PEMASARAN UKM KULINER DAERAH DI JABODETABEK - Iha Haryani Hatta (Institute of Research and Community Outreach - Petra Christian University, 2014)
Indonesian traditional culinary businesses must face a competitive environment due to the influx of imported food products and the change of culinary taste of the younger generation. Therefore, it is necessary for small scale culinary businesses to enhance their capacity to be able to compete in the business by taking autonomous, proactive, innovative and risk-taking steps that leads to better Marketing Capability. In this research Entrepreneurship Orientation is observed through seven dimensions namely: product capability, price, place, promotion, people, process and physical evidence. This research involved 200 culinary SMEs in the area of Jabodetabek (Jakarta, Bogor, Depok, Tangerang, Bekasi) that were randomly selected as respondents and this research concluded that there is a positive effect from autonomous, innovative and risk-taking efforts towards the Marketing Capability. Meanwhile proactive effort has a negative effect towards the Marketing Capability of the Culinary SMEs in Jabodetabek. The Marketing Capability is indicated by the promotion capability, human resources capability, process capability, and the capability of the chosen place or venue for the culinary business.